2023
DOI: 10.1212/wnl.0000000000207446
|View full text |Cite
|
Sign up to set email alerts
|

Twenty-Year Disparity Trends in United States Stroke Death Rate by Age, Race/Ethnicity, Geography, and Socioeconomic Status

Abstract: BackgroundIn 2017 the CDC issued an alert that, after decades of consistent decline, the stroke death rate levelled off in 2013, particularly in younger individuals and without clear origin. The objective of this analysis is to understand whether social determinants of health have influenced trends in stroke mortality.MethodsWe performed a longitudinal analysis of county-level ischemic and hemorrhagic stroke death rate per 100,000 adults, from 1999-2018 using a Bayesian spatiotemporally smoothed CDC dataset st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 39 publications
(58 reference statements)
1
4
0
Order By: Relevance
“…Numerous studies have reported the racial disparity in IVT utilization rate [1,10,11,37,38]. We observed the same phenomenon (7% in non-white vs. 13% in white; p = 0.042), which was not surprising given the delay in ED arrival in the case of the non-white group.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Numerous studies have reported the racial disparity in IVT utilization rate [1,10,11,37,38]. We observed the same phenomenon (7% in non-white vs. 13% in white; p = 0.042), which was not surprising given the delay in ED arrival in the case of the non-white group.…”
Section: Discussionsupporting
confidence: 81%
“…Some patients were missing the race/ethnicity categorization in the GWTG and the medical records and were assumed to be non-white if their country of origin was not the United States or if their primary language was not English. We did not have data on important SODH that have been found to be important predictors of stroke incidence and outcome, such as income, level of education, employment, housing, and insurance status [1,4]. We were unable to follow the recommended disaggregation of races/ethnicities [54] and combined all non-white patients in one group because of the small sample size, which might have obscured important inter-racial differences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lifestyle changes such as decreased physical activity and increased intake of highcaloric food, salt, saturated fats, and trans fatty acids have increased the prevalence of thromboembolic or atherosclerotic events, such as acute ischemic stroke (AIS) and myocardial infarction, in the Western world in recent decades and, more recently, in developing countries [1]. However, due to better preventative measures such as antithrombotic drugs, anticoagulation, statins, antidiabetics, and antihypertensives, stroke incidence and stroke mortality have decreased over the last decades but may be reversing again [2]. Despite these trends, AIS remains one of the five most common causes of death in the US and Europe [3].…”
Section: Introductionmentioning
confidence: 99%
“…14,15 A related study demonstrated that socially disadvantaged US counties had significantly higher stroke mortality than counties with low area-level social deprivation. 16 Similarly, historical redlining was associated with modern-day stroke prevalence in New York City independently of contemporary individual measures of socioeconomic status. 17 Data from the Black Women's Health Study suggested that Black women who experienced interpersonal racism had higher stroke incidence than those without prior experiences of racism, 18 thus establishing a direct link between interpersonal racism and stroke incidence later in life.…”
mentioning
confidence: 96%